Paul, Apostle of God's glory in Christ : a Pauline theology - Schreiner, Thomas R. (Downers Grove IVP Academia, 2020)
"How should students of Scripture engage with discerning the shape of Paul's thought? In this second edition of a trusted resource, Thomas R. Schreiner seeks to unearth Paul's worldview by observing what Paul actually says in his writings and laying out the most important themes and how they are connected. While thoroughly informed by contemporary Pauline studies, Schreiner offers an accessible account of Paul's theology"--
Includes bibliographical references and indexes.
Keywords: Bible. -- Theology